2020
DOI: 10.1038/s41598-020-64661-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility between Bifidobacteria Targeting and Changes in the Acoustic Environment of tumor Tissue for Synergistic HIFU

Abstract: High intensity focused ultrasound (HIFU) has been recently shown as a rapidly developing new technique for non-invasive ablation of local tumors whose therapeutic efficiency can be significantly improved by changing the tissue acoustic environment (AET). Currently, the method of changing AET is mainly to introduce a medium with high acoustic impedance, but there are some disadvantages such as low retention of the introduced medium in the target area and a short residence time during the process. In our strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It also induces cell death through autophagy ( Engevik et al, 2019 ). Bifidobacterium can increase anti-PD-L1 and inhibit tumor volume by inducing anti-inflammatory activity of macrophages and dendritic cells ( Xu et al, 2020 ). Probiotics such as Lactobacillus and Bifidobacterium inhibit the growth of colorectal cancer by suppressing inflammation and angiogenesis, and enhance the intestinal barrier function by secreting short-chain fatty acids (SCFAs) ( Koh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also induces cell death through autophagy ( Engevik et al, 2019 ). Bifidobacterium can increase anti-PD-L1 and inhibit tumor volume by inducing anti-inflammatory activity of macrophages and dendritic cells ( Xu et al, 2020 ). Probiotics such as Lactobacillus and Bifidobacterium inhibit the growth of colorectal cancer by suppressing inflammation and angiogenesis, and enhance the intestinal barrier function by secreting short-chain fatty acids (SCFAs) ( Koh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 3 However, the US radiation energy decays exponentially with increasing tissue depths and blood perfusion rates, which leads to insufficient energy accumulation in focal region, thus compromising the therapeutic efficiency of HIFU. 4 Classical strategy to strengthen ablation efficacy of HIFU is to increase the acoustic power or prolong the operation duration, but these options may lead to adverse biological effects such as transient pain, skin or nerve injury. 5 6 Some investigations have confirmed that the introduction of synergistic agents (SAs) is an efficient and alternative route to enhance HIFU surgical efficacy.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Thus, bacteria such as Bifidobacterium have been considered as potential markers that may aid in the identification of tumour masses and facilitate tumour targeting diagnosis and treatment ( 74-76 ). When using Bifidobacterium as the targeting agent for tumour tissue, it could be either directly cross-linked to the delivery platform acting as an arch on a ‘bacterial robot’ or allowed to colonize in the tumour mass first, then another Bifidobacterium targeting NP can be utilized to achieve indirect targeting of the tumour ( 77 ). Jiang et al ( 78 ) compared these targeting strategies and found that when combined with HIFU ablation, the indirect targeting method was more efficient than cross-linking bacteria with NP payloads.…”
Section: Nano-therapeutics For Hifu-based Cancer Treatmentmentioning
confidence: 99%